Selection of display materials for using in the Shanghai Museum East by the Oddy Test - Shen Jingyi (E3S Web of Conferences)
The Shanghai Museum East has been open to the public in 2024. Since the collections are sensitive to indoor air contaminants such as organic acids, volatile organic compounds and formaldehyde, a series of work was done in order to ensure the qualification of environment in the galleries and showcases. As the showcases are made of different materials including boards, fabrics, sealants, sealing strips, etc., the reliability of these materials are directly relevant to the safety of collections. Established and adopted by the British Museum, the Oddy Test is a simple and intuitive method for judging the reliability of unknown display materials. The test was conducted to screen out the permanently usable materials in over one hundred potential candidates in the showcase preparation stage. The case of nine typical materials was studied and introduced in this work. The result indicates the most suspicious materials, as some kinds of organics like sealants, fabrics, boards, etc. Staffs, conservators and researchers can learn from this study to have a preliminary judgment on the selection of unknown display materials.